Parkinson’s Disease Motor Subtypes Show Different Responses to Long-Term Subthalamic Nucleus Stimulation - Xu, Cuiping; Zhuang, Ping; Hallett, Mark; Zhang, Yuqing; Li, Jianyu; Li, Yongjie (Frontiers in Human Neuroscience, 2018)
Background and purpose: Subthalamic nucleus deep brain stimulation (STN DBS) is well established for the treatment of advanced Parkinson's disease (PD), substantially improving motor symptoms, quality of life and reduction in dopaminergic medication requirement for a long time. However, whether chronic STN DBS produces different effects on PD motor subtypes is not known. This retrospective study aimed to evaluate the long-term effects of STN DBS for PD motor subtypes. Method: Eighty patients undergoing STN DBS were included. The Unified Parkinson's Disease Rating Scale (UPDRS) were performed in on- and off-medication/on- and off-stimulation conditions. Akinetic-rigid type (ART), tremor-dominant type (TDT) and mixed type (MT) were classified based on preoperative UPDRS III subscores in "Off" medication. Pre- and postoperative comparisons were performed. Results: After 4.9 years, STN DBS produced significant improvement in UPDRS III total score and subscores of tremor, rigidity, and bradykinesia in “Off” medication for ART group, less for MT group, and least for TDT group. , UPDRS II and III total score and other subscores did not improve during “On” medication. However, all groups improved substantially, and the improvement in tremor was sustained for both “On and Off ”medication after years. Long-term STN DBS did not improve swallowing and speech in any of the subtypes. Conclusions: The data confirm that PD is heterogeneous. Long-term STN DBS produced best effects on bradykinesia/rigidity in “Off medication” and tremor in “On and Off medication”. There are differences in response by group, but some of the differences are explained by the fact that more severe symptoms at baseline tend to have greater improvement. The findings support the idea that the ART mainly involves the basal ganglia-thalamo-cortical pathway whereas the TDT involves more another circuit, likely the cerebellar-thalamo-cortical pathway.